Transformation of Tax Services: Improving Tax Return Compliance Through Socialization and Assistance Efforts at Agency X - Dita Selsabillah; Fitri Purnamasari (Dinasti Publisher, 2025)
Tax is a mandatory contribution paid by the people to the state. The benefits of taxes are not directly felt by the taxpayers but are used for the common good. Taxpayers must report their Annual Tax Return through DJP Online using the E-Filing feature by March 31. However, there are issues within Agency X, where some employees do not report their Annual Tax Return. The identified reasons include limited technological skills among senior employees, the assumption that Daily Casual Workers (THL) are not required to report, and incomes below the Non-Taxable Income (PTKP) threshold. The purpose of this study is to improve compliance with Annual Tax Return reporting in the agency and ensure that all taxpayers fulfill their obligations. The research method used falls into the category of qualitative research, implemented through a case study, in accordance with Creswell's (1988) definition, which explores cases within a specific period by collecting detailed data from relevant sources. Primary data was obtained through interviews and direct observation, while secondary data was collected from documents and photographs. The research findings indicate that tax education and assistance related to Annual Tax Return reporting can enhance compliance within Agency X. There was a significant increase in reporting compliance compared to the previous year.